Dietary organic zinc supplementation modifies the oxidative genes via RORγ and epigenetic regulations in the Ileum of broiler chickens exposed to high-temperature stress - Adam, S.A.; Muniyappan, M.; Hao Huang; Ennab, W.; Hao-Yu Liu; Ahmed, A.A.; Ming-an Sun; Dessie, Tadelle; In Ho Kim; Yun Hu; Xugang Luo; Demin Cai (MDPI, 2024)
Heat stress (HS) is a significant concern in broiler chickens, which is vital for global meat supply in the dynamic field of poultry farming. The impact of heat stress on the ileum and its influence on the redox homeostatic genes in chickens remains unclear. We hypothesized that adding zinc to the feed of heat-stressed broilers would improve their resilience to heat stress. However, this study aimed to explore the effects of organic zinc supplementation under HS conditions on broiler chickens’ intestinal histology and regulation of HS index genes. In this study, 512 Xueshan chickens were divided into four groups: vehicle, HS, 60 mg/kg zinc, and HS + 60 mg/kg zinc groups. Findings revealed that zinc supply positively increased the VH and VH: CD in the ileum of the broilers compared to the HS group, while CD and VW decreased in Zn and HS+Zn supplemented broilers. Zn administration significantly increased superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), and decreased the enzymatic activities of reactive oxygen species (ROS) and malondialdehyde (MDA) compared to the HS group. In addition, Zn administration significantly increased relative ATP, complex I, III, and V enzyme activity compared to the HS group. Furthermore, the expression of acyl-CoA synthetase long-chain family member 4 (ACSL4), lactate transporter 3 (LPCAT3), peroxiredoxin (PRX), and transferrin receptor (TFRC) in the protein levels was extremely downregulated in HS+Zn compared to the HS group. Zn supply significantly decreased the enrichment of RORγ, P300, and SRC1 at target loci of ACSL4, LPCAT3, and PRX compared to the HS group. The occupancies of histone active marks H3K9ac, H3K18ac, H3K27ac, H3K4me1, and H3K18bhb at the locus of ACSL4 and LPCAT3 were significantly decreased in HS+Zn compared to the HS group. Moreover, H3K9la and H3K18la at the locus of ACSL4 and LPCAT3 were significantly decreased in HS+Zn compared to the HS group. This study emphasizes that organic Zn is a potential strategy for modulating the oxidative genes ACSL4, LPCAT3, PRX, and TFRC in the ileum of chickens via nuclear receptor RORγ regulation and histone modifications.